Holistic PAUD Concept: Integrating Aspect Social and Emotional Cognitive - Miya Rahmawati (Bulletin of Early Childhood, 2025)
This research aims describe implementation early childhood education (PAUD) with a holistic approach that integrates aspect cognitive, social, and emotional, as well as analyze its impact on child development. The research background starts from the phenomenon that most of PAUD institutions still focused on academic achievement, while social- emotional development has not received attention attention balanced. This research uses a qualitative method with a case study approach in one of the Early Childhood Education Institutions in Lubuk Linggau, involving early childhood education teachers, children aged 4–6 years, and parents. Data were collected through learning observations, in-depth interviews, and documentation of child development. analyzed thematically. The results of the study show that holistic learning is able to improve children's cognitive development through exploratory activities, problem solving, and concept recognition ; supporting social skills through cooperation, taking turns, and value opinion friends ; and strengthen ability emotional in recognizing and managing Healthy emotions. Children with good social- emotional skills have been shown to be more focused and motivated, which has a positive impact on academic achievement. cognitive. The success of holistic learning is greatly influenced by the cooperation between teachers and parents in creating stimulation consistent at school and home. This research strengthens the theories of Piaget, Vygotsky, and Erikson on the integration of child development as well as provide practical recommendations for development holistic PAUD curriculum.